COMMUNITY EMPOWERMENT IN THE SOCIAL, ECONOMIC, AND RELIGIOUS FIELDS BASED ON LOCAL WISDOM - Heriyansyah, Heriyansyah; Zakaria, Aceng; Samsuddin, Samsuddin; Marsilah, Nyai Siti; Aini, Farah; Rahmah, Firda Aulia (STAI Al-Hidayah Bogor, 2024)
This article is being published on behalf of one of the tridharma activities of the university, namely, Dedication to the Society. (PkM). This service to the community is an annual routine activity carried out by a lecturer. The PkM activities take place in the village of Cihideung Ilir, Ciampea district, Bogor district. The theme of the event is the empowerment of the community in the social, economic and religious fields based on local wisdom. In short, this article contains an analysis of the development of science and creativity that is very important developed as one of the main tasks of Tridharma College. that the implementation of the basic duties of the lecturer is the duty to carry out the field of devotion to the society in addition to the performance of the tasks in the fields of teaching and research. The method used in this writing is qualitative descriptive with an analysis approach of local wisdom phenomena. This research found that there is a great benefit of the activities of the PkM for society that is the occurrence of the process of integration of science applied in the midst of the society based on internal needs in order to answer the problems that must be solved both in the social, economic and religious spheres.